Influence of previous pesticide use on Tetranychus urticae and Phytoseiulus persimilis (Acari: Tetranychidae, Phytoseiidae) from strawberry crops in the north of Morocco - Lagziri, Mariam; Benicha, Mohamed; M'rabet, Rachid; El Amrani, Amal (Biotechnologie, agronomie, société et environnement, 2015)
Effects of recommended doses of five common pesticides in the strawberries of Loukkos area (Morocco) were tested on the two-spotted spider mite Tetranychus urticae and its predatory mite Phytoseiulus persimilis. Laboratory study assessed the contact toxicity of one avennectin miticide (abamectin), two pyrethrinoid insecticide-acaricides (bifenthrin and lambda-cyalothrin), and two fungicides: firstly, mancozeb, winch belongs to the dithiocarbamates family of chemicals and secondly, hexaconazole, of the triazole family. The aim of the present study was to test in laboratory conditions the effect of five pesticides on the two-spotted spider mite, T. urticae and its predatory mite, P. persimilis. The five pesticides tested were those most frequently applied for at least two years on strawberries at the experimental site. Bioassays were performed with populations of mites originating from different plots with various crop protection backgrounds. The first group of plots had been repeatedly treated with the five tested pesticides during a two-year period, the second group had been moderately treated, and the third had been treated once with the tested pesticides. Our results showed that the tested pesticides provided effective control of T. urticae but that they were not compatible with use on the predatory mite P. persimilis, as these particular mites did not usually come into contact with these products. On the other hand, in plots where pesticides had been used for a long time, the susceptibility of P. persimilis populations to these products was significantly reduced. If the tested pesticides are to be considered for integrated pest control programs in plots where they have been used for a long time and where P. persimilis is present, their use should be minimized in plots where they have never or rarely been applied.